Learning Transformation Using Sap Successfactor Learning Management System In Pandemic Era - Achmad Sirrul Atho’ (Institut Manajemen Wiyata Indonesia & Asosiasi Peneliti Manajemen Indonesia, 2023)
The COVID-19 pandemic situation has changed everything, including the way of learning for employees. Prior to the pandemic, learning for employees was carried out conventionally face-to-face in class. However, after a pandemic occurs, learning cannot be done in the same way so that other ways need to be done to maintain the continuity of learning. One way is to use the SAP Successfactor (SF) platform which has a Learning Management System (LMS) module. PT Semen Indonesia (Persero) Tbk. (SIG) uses the SF-LMS that provides a space for employees to do online learning. SIG captures the business needs first and then design the LMS module. Employees can enter the SF-LMS and access the learning materials that have been provided. Learning materials can be provided in various forms, including documents, video learning, and audio learning so that employees get many variations of quality learning models according to what they like. This supports pillar number four, namely quality education in the Sustainable Development Goals (SDGs). The successful implementation of the SF-LMS must be accompanied by evaluations from the system and employees perspective so that continuous improvements can be made. And finally, the learning objectives can be achieved.